THE INFLUENCE OF PRODUCT ATTRIBUTES, CONSUMER ATTITUDE AND CONSUMER INTEREST ON THE PURCHASE DECISION OF LOCAL ORANGE FRUIT IN MALANG CITY - Erika Eldisthia; Budi Setiawan; Abdul Wahib Muhaimin (Socio-Economics/Agribusiness Department, 2023)
This study aims to determine the effect of product attributes, consumer attitudes and consumer interest on purchasing decisions of local citrus fruits on consumers in Malang City. This research method is descriptive quantitative using Structural Equation Modeling (SEM) analysis with Warp Partial Least Square (WarpPLS) approach. Primary data was obtained through filling out a questionnaire as an online interview media. Meanwhile, secondary data was obtained through literature studies from various related sources. Sampling was done based on non-probability sampling technique and 124 samples were selected as respondents in this study. The results showed that product attributes had a positive and significant effect on consumer attitudes and interests, consumer attitudes had a positive and significant effect on purchasing decisions, and positive and significant consumer interest on purchasing decisions.